Religions of the ancient Near East - Snell, Daniel C. (New York : Cambridge University Press, 2011)
"This book is a history of religious life in the Ancient Near East from the beginnings of agriculture to Alexander the Great's invasion in the 300s BCE"--
"This book is a history of religious life in the Ancient Near East from the beginnings of agriculture to Alexander the Great's invasion in the 300s BCE. Daniel C. Snell traces key developments in the history, daily life, and religious beliefs of the people of Ancient Mesopotamia, Egypt, Israel, and Iran. His research investigates the influence of those ideas on the West, with particular emphasis on how religious ideas from this historical and cultural milieu persist to influence the way modern cultures and religions view the world. Designed to be accessible to students and readers with no prior knowledge of the period, the book uses fictional vignettes to add interest to its material, which is based on careful study of archeological remains and preserved texts. The book will provide a thoughtful summary of the Ancien Near East and includes a comprehensive bibliography to guide readers in further study of related topics"--
Defining time and space -- Early inklings -- Gods, gods, gods -- Cities, states, and god -- The lure of Egypt, 4000-1400 BCE -- The gods of Egypt -- The Akhenaten dream, 1350-1300 BCE -- Practice in Egypt -- The international age, 1400-1000 BCE -- Gods and people -- The Lord is one : Israel in its environment -- The turning -- The good god and the bad god -- The lands of Baal -- Greece, Etruria, Rome, and conveying traditions -- The dead hand of the past and the living God -- Experiencing ancient Near Eastern religion.
Includes bibliographical references (p. 169-176) and index.
Description based on print version record.
Keywords: Middle East -- Religion; Middle East -- Religious life and customs; Electronic books; RELIGION / History